Five new species of Myrsidea Waterston (Phthiraptera: Menoponidae) from bristlebills and greenbuls (Passeriformes: Pycnonotidae) in Ghana - Johnson, Kevin P.; Price, Roger D. (Zootaxa, 2006)
Five new species of chewing lice of the genus Myrsidea Waterston from the passerine family Pycnonotidae are described and illustrated. They and their type hosts are: M. masoni ex Bleda eximius (Hartlaub), M. chesseri ex Criniger barbatus (Temminck), M. palmeri ex Andropadus curvirostris Cassin, M. wombeyi ex Bleda syndactylus (Swainson), and M. marksi ex Phyllastrephus albigularis (Sharpe). These represent the first species of pycnonotid Myrsidea to be described from African hosts. Partial mitochondrial cytochrome oxidase I (COI) sequences were collected for these species and additional species of Myrsidea, which support the genetic distinctiveness of these new species.